Comparing patient-perceived and physician-perceived remission and low disease activity in psoriatic arthritis: an analysis of 410 patients from 14 countries. Issue 2 (15th November 2018) - Gorlier, Clémence; Orbai, Ana-Maria; Puyraimond-Zemmour, Déborah; Coates, Laura C; Kiltz, Uta; Leung, Ying-Ying; Palominos, Penelope; Cañete, Juan D; Scrivo, Rossana; Balanescu, Andra; Dernis, Emmanuelle; Tälli, Sandra; et al.
Abstract : Background: The objective was to compare different definitions of remission and low disease activity (LDA) in patients with psoriatic arthritis (PsA), based on both patients' and physicians' perspectives. Methods: In ReFlap (Remission/Flare in PsA; NCT03119805 ), adults with physician-confirmed PsA and >2 years of disease duration in 14 countries were included. Remission was defined as very low disease activity (VLDA), Disease Activity index for PSoriatic Arthritis (DAPSA) ≤4, and physician-perceived and patient-perceived remission (specific question yes/no), and LDA as minimal disease activity (MDA), DAPSA <14, and physician-perceived and patient-perceived LDA. Frequencies of these definitions, their agreement (prevalence-adjusted kappa), and sensitivity and specificity versus patient-defined status were assessed cross-sectionally. Results: Of 410 patients, the mean age (SD) was 53.9 (12.5) years, 50.7% were male, disease duration was 11.2 (8.2) years, 56.8% were on biologics, and remission/LDA was frequently attained: respectively, for remission from 12.4% (VLDA) to 36.1% (physician-perceived remission), and for LDA from 25.4% (MDA) to 43.9% (patient-perceived LDA). Thus, patient-perceived remission/LDA was frequent (65.4%). Agreement between patient-perceived remission/LDA and composite scores was moderate to good (kappa range, 0.12–0.65). When patient-perceived remission or LDA status is used as reference, DAPSA-defined remission/LDA and VLDA/MDA had a sensitivity of 73.1% and 51.5%, respectively, and a specificity of 76.8% and 88.0%, respectively. Physician-perceived remission/LDA using a single question was frequent (67.6%) but performed poorly against other definitions. Conclusion: In this unselected population, remission/LDA was frequently attained. VLDA/MDA was a more stringent definition than DAPSA-based remission/LDA. DAPSA-based remission/LDA performed better than VLDA/MDA to detect patient-defined remission or remission/LDA. Further studies of long-term outcomes are needed.